Efektivitas Pembelajaran Dengan Kegiatan Praktikum Berbasis Jelajah Alam Sekitar (JAS) di SMA Negeri 3 Balaesang Kecamatan Balaesang Kabupaten Donggala Sulawesi Tengah - Hariyati, Hariyati; Vlorensius, Vlorensius; Adhani, Aidil (Program Studi Pendidikan Biologi Universitas Borneo Tarakan, 2025)
Achieving learning objectives requires a strong understanding of the learning approach. One method that can aid in the learning process is the JAS approach, which places a strong emphasis on learning activities that are relevant to everyday life and the environment as a source of knowledge. The aim of this study was to assess how well students in class X of SMAN 3 Balaesang learned through practical activities centred on investigating the surrounding environment. This study employed a quasi-experimental research design using quantitative research methods. Learning outcome assessments and learning motivation questionnaires were used to gather data. 56 participants were selected from two classes XC, which included 29 students as a control group and XD, which included 27 students as an experimental group for this study's sample. The z test was used to determine the classical completeness of the control and experimental classes, and the independent sample t-test was utilized to determine the difference in learning outcomes between the two groups. The study's findings demonstrated that the experimental class utilizing JAS and the control class using the conventional approach had different learning outcomes, with the JAS-using students achieving better learning outcomes than the traditional approach. According to the z-test results, less than 70% of students in the control class using the traditional method obtained the KKM score, whereas more than 70% of students in the experimental class utilizing JAS received a passing mark. Students in the experimental class were more motivated to learn. than those in the control group.